Sistematización de la gestión de seguimiento a graduados - Boada Suntaxi, Verónica Paola (2018)
This document will provide concrete and clear information on the management that tracks graduates of the communication career, in such a way that the reader has knowledge about the graduates in communication and about the area and its work. Systematization is a set of ideas that help an educational process of data collection or experiences, with the intention of improving aspects that have not yet been worked and consider previous practices or information, being able to be incorporated into Future actions. The approach that guides this process of systematization is of a qualitative nature and is reflected in a short report, which presents the activities that are carried out around the follow-up to graduates through their academic, professional and personal experiences in Benefit to graduates. The collection of information from the follow-up management to graduates aims to analyses the data and information collected in such a way as to select aspects through a legislative framework, links of interest, culture of belonging and vocational training About graduates. This report will help to understand what the Social communication career brings to its students and graduates throughout their academic and professional career along with the values and knowledge that permanently forge the student Salesian.